Specification for bitumen road emulsions ( anionic and cationic ) Part 1. Requirements (BSI, 1973)
Bitumens, Roads, Construction materials, Anions, Cations, Wearing courses (roads), Emulsions, Pavements (roads), Composition, Marking, Life (durability), Stability, Viscosity measurement, Sampling methods, Sieving, Water content determination, Binding agents, Test equipment, Viscometers, Coagulation, Sedimentation